Spatial planning through the lens of technological modes - Дина Саттарова; Елизавета Ото; Марина Иванкова; Екатерина Крючкова (Проект Байкал)
The article substantiates the possibility of creating a systematic approach to the analysis of countries’ experience in spatial planning through the lens of technological modes. The basis for the creation of such an approach is the proposed conceptual scheme of validity of the choice of directions for analysing spatial planning systems. It is shown that the close relationship between the level of the country’s economy and the phase of its technological mode allows us to propose a classification of countries and possible directions for analysing their spatial planning systems. The authors substantiate the objectivity of the obtained comparability of countries when analysing their spatial planning systems.